1998
DOI: 10.1128/jvi.72.1.542-549.1998
|View full text |Cite
|
Sign up to set email alerts
|

Interferon Induction as a Quasispecies Marker of Vesicular Stomatitis Virus Populations

Abstract: The interferon (IFN)-inducing capacity of different isolates of vesicular stomatitis virus (VSV) of the Indiana (IN) and New Jersey (NJ) serotypes were measured to assess the extent of variability of this phenotype. Over 200 preparations of wild-type field isolates, laboratory strains, and plaque-derived subpopulations were examined. Marked heterogeneity was found in the ability of these viruses to induce IFN, covering a 10,000-fold range. A good fit to a normal distribution for the log of the IFN yields sugge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
1

Year Published

1998
1998
2009
2009

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(27 citation statements)
references
References 44 publications
3
23
1
Order By: Relevance
“…*, Significant difference compared to polyI:C treated and isolate 3 infected cells (P < 0.05). vesicular stomatitis virus (VSV) (Marcus et al, 1998). In contrast to the results presented herein, a study using the European PRRSV strains SDRPI and SDRPII found no strain differences in IFN-a sensitivity or induction, despite differences in clinical virulence (Albina et al, 1998a).…”
Section: Discussioncontrasting
confidence: 95%
See 1 more Smart Citation
“…*, Significant difference compared to polyI:C treated and isolate 3 infected cells (P < 0.05). vesicular stomatitis virus (VSV) (Marcus et al, 1998). In contrast to the results presented herein, a study using the European PRRSV strains SDRPI and SDRPII found no strain differences in IFN-a sensitivity or induction, despite differences in clinical virulence (Albina et al, 1998a).…”
Section: Discussioncontrasting
confidence: 95%
“…For viruses such as Sendai virus and VSV, low IFNinducing strains have been shown to suppress IFN induction of high IFN-inducing strains of the same virus (Marcus et al, 1998;Mattana and Viscomi, 1998). In the present study, the levels of PRRSV IFN induction were typically too low to use in a similarly designed suppression experiment.…”
Section: Discussionmentioning
confidence: 62%
“…The primary conclusion from published data is that RNA viruses (including viruses which use RNA as replicative intermediate such as hepatitis B virus) behave largely as predicted by the quasispecies model of molecular evolution. Quasispecies swarms, and not any sort of defined genetic entity, are those that replicate in infected hosts as they produce disease Domingo et al, 1995;Marcus et al, 1998).…”
Section: Trying To Cope With Indeterminationmentioning
confidence: 99%
“…The problem is challenging in part because potentially important cell-to-cell differences will be masked by standard culture methods that only provide average-virus or average-cell behaviors. We address this issue by measuring virus progeny yields from single cells infected by single particles of vesicular stomatitis virus (VSV), an RNA virus that exists as a quasi-species (Cuevas et al, 2005;Marcus et al, 1998;and Steinhauer et al, 1989) and ranks among the most widely investigated systems for the study of viral evolution Elena et al, 1996;Holland et al, 1982;Nichol et al, 1989;Novella et al, 1999Novella et al, , 2007Quer et al, 2001;and Sanjuan et al, 2007). We infect cells with a recombinant strain of VSV that expresses green-fluorescent protein, and we employ fluorescence-activated cell sorting (FACS) to isolate individual cells that have been infected by single virus particles.…”
Section: Introductionmentioning
confidence: 99%